Green synthesis of magnetic mesoporous carbon from waste-lignin and its application as an efficient heterogeneous Fenton catalyst. (20th February 2021) - Xu, Fang; Lu, Qinwei; Li, Kunpeng; Zhu, Ting-Ting; Wang, Wei-Kang; Hu, Zhen-Hu
Abstract: Various pretreatment strategies have been widely employed for the removal of lignin and made great progress in the utilization of cellulose from lignocellulosic biomass. However, how to make full use of the lignin component is still a great challenge. In this work, a novel magnetic mesoporous carbon (MMC, Fe3 O4 @mesoporous carbon) was successfully fabricated using waste-lignin and FeCl3 as precursors. The chemical/physical properties of MMC samples were systematically characterized by various characterization techniques. The mesoporous structure of MMC with average pore size of 3.86 nm and specific surface area of 138 m 2 /g was further confirmed by Brunauer-Emmet-Teller (BET) analysis. The saturation magnetization values of MMC samples increased from 7.28 to 36.55 emu/g with the increase of FeCl3 dosage. MMC also showed superior reusability in recycling experiments. The catalytic mechanism was revealed through reactive oxygen species quenching experiments and the generation of hydroxyl radicals (OH) was further identified by electron paramagnetic resonance spectroscopy. This work provides a green and sustainable strategy for the fabrication of high-performance heterogeneous Fenton catalyst as well as all-round utilization of waste lignin. Graphical abstract: Image 1 Highlights: Magnetic mesoporous carbon was fabricated using waste-lignin and FeCl3 as precursors. Magnetic mesoporous carbon was used as an efficient heterogeneous Fenton catalyst. Fe3 O4 plays a dual role of serving as catalytic sites and enabling magnetic isolation. Mesoporous carbon was designed to work as a confined reactor and to protect Fe3 O4 .